Comparative Study of Education: Islamic Education System of Indonesia and Brunei Darussalam - Rahmania, Elvina; Saprianingsih, Sri Whenti; Maryamah, Maryamah; Oviyanti, Fitri (Journal of Educational Sciences, 2025)
This study presents the differences between the Islamic education systems of Indonesia and Brunei Darussalam. These two Southeast Asian countries have unique characteristics in their approach to Islamic education. The research method used is descriptive qualitative with literature data collection techniques (library research). The results of the study show that this measurement provides rich insight into the dynamics of Islamic education and can be a reference for both countries in efforts to improve the quality of Islamic education. The fundamental difference lies in the emphasis given to religious studies in Islamic countries such as Indonesia and Brunei Darussalam. Religious studies are highly emphasized to form people who are moral, ethical, and have noble personalities. This reflects Islamic values that are an integral part of education and daily life in the country. However, both have similarities in including religious education in the curriculum as part of an effort to build students' character and morals. The main goal is to create a young generation that has strong moral values and good personalities, so that they can make a positive contribution to society and the nation in the future.